Alterations in Malondiadehyde and membrane potential in anaemic patients - Somtochukwu Mercy Onwuagba; Nnodim Johnkennedy (Al Ameen Medical College, 2017)
Background: Anaemia is a decrease in the total amount of red blood cells (RBCs) or hemoglobin in the blood and has a lowered ability of the blood to carry oxygen. Aim and Objectives: To determine the level of Malondiadehyde and membrane potential in anaemic patients attending General Hospital Owerri. Materials and methods: Fifty confirmed anaemicc patients and fifty apparently healthy subjects (control) between the ages of 10 to 20 years were selected in this study. Serum malondialdehyde (MDA) and membrane potential were estimated using standard methods. Results: There serum levels of MDA was significantly increased in anaemic patients when compared to control (p<0.05). While the membrane potential was significantly decreased in anaemic patients when compared with the control (P< 0.05). Conclusion: These could probably imply that anaemic patients could be prone to oxidative stress as well as have low cell activity.